1982
DOI: 10.1002/j.1552-4604.1982.tb02161.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Renal Perfusion During Treatment of Essential Hypertension with the Beta Blocker Nadolol

Abstract: Several beta-adrenergic antagonists impair renal perfusion during treatment of hypertension in man. The acute and chronic effects of a new noncardioselective beta blocker, nadolol, on renal hemodynamics, intravascular volume, and renal electrolyte excretion were studied in 10 men with essential hypertension. Oral nadolol normalized systemic blood pressure without impairment of glomerular filtration rate or renal blood flow, indicating preserved renal blood flow and glomerular filtration rate autoregulation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Accordingly, the fraction of c put reaching the renal circulation s increased during treatment with nad( over, glomerular filtration rate, urin urinary sodium excretion and bo remained stable. Our findings confir O'Connor et al (1982) who also demonstrated preserved renal perfusion during treatment of essential hypertension with nadolol and the observation of Textor et al (1982) Warren et al, 1981), does not suppress the renal production of vasodilatory kinins, which could have protected against a decrease in renal blood flow. It has also been suggested that nadolol might have dopaminergic properties (Epstein & Oster, 1982).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accordingly, the fraction of c put reaching the renal circulation s increased during treatment with nad( over, glomerular filtration rate, urin urinary sodium excretion and bo remained stable. Our findings confir O'Connor et al (1982) who also demonstrated preserved renal perfusion during treatment of essential hypertension with nadolol and the observation of Textor et al (1982) Warren et al, 1981), does not suppress the renal production of vasodilatory kinins, which could have protected against a decrease in renal blood flow. It has also been suggested that nadolol might have dopaminergic properties (Epstein & Oster, 1982).…”
Section: Discussionsupporting
confidence: 87%
“…After chronic administration of nadolol to patients with essential hypertension, either an increase (Britton etal., 1981;Danesh & Brunton, 1981), a decrease (O'Callaghan et al, 1983), or no change of renal blood flow (O'Connor et al, 1982;Textor et al, 1982;Waal-Manning & Hobson, 1980) have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…After an initial intravenous bolus of 1.4 g inulin, a continuous infusion of inulin was started at 1 mL/min (1 g/100 mL in half-normal saline; ie, 10 mg/min) for 180 minutes. 17 One hour after the start of the inulin infusion, the subjects voided and urine was discarded, before the baseline clearance period. In the next 30-minute (baseline) period, blood was drawn for measurement of blood urea nitrogen, creatinine, electrolytes, lithium, amino acids, inulin, glucose, and insulin, and a timed urine test was collected for measurement of creatinine, electrolytes, lithium, inulin, nitrate/nitrite (as an index of NO production), and cGMP.…”
Section: Amino Acid Infusion and Renal Clearance Protocolmentioning
confidence: 99%
“…Inulin was measured according to the alkali-stable spectrophotometric method, as we previously described. 17 Urinary cGMP was measured with radioimmunoassay (DuPont-New England Nuclear). To measure urinary nitrate/nitrite (NO x ), nitrate (NO 3 ) was first converted to nitrite (NO 2 ) with Escherichia coli nitrate reductase in vitro 18 ; nitrite was then measured with the Griess spectrophotometric reaction (monitoring absorbance at 546 nm).…”
Section: Assaysmentioning
confidence: 99%
“…Similar results were obtained with propranolol treatment Westaby et al, 1984), not surprisingly, since both drugs share the same pharmacological activity and site of action. In the present and in the previous studies we used a dose of nadolol ranging from 40 to 160 mg day-1, as it is commonly administered to patients with arterial hypertension (O'Connor et al, 1982). The between patients differences are likely to depend on baseline adrenergic tone of the patients, and not on liver function, since the drug does not undergo a significant hepatic metabolism.…”
Section: Resultsmentioning
confidence: 99%